Pain in knee osteoarthritis is associated with variation in the neurokinin 1/substance P receptor (TACR1) gene. (11th May 2017) - Warner, S.C.; Walsh, D.A.; Laslett, L.L.; Maciewicz, R.A.; Soni, A.; Hart, D.J.; Zhang, W.; Muir, K.R.; Dennison, E.M.; Leaverton, P.; Rampersaud, E.; Cooper, C.; et al.
Abstract: Background: Substance P (SP) is a pain‐ and inflammation‐related neuropeptide which preferentially binds to the neurokinin receptor 1 (NK1 ). SP and NK1 receptors have been implicated in joint pain, inflammation and damage in animal models and human studies of osteoarthritis (OA). The aim of this study was to test if genetic variation at the neurokinin 1 receptor gene ( TACR1 ) is associated with pain in individuals with radiographic knee OA. Methods: Participants from the Genetics of OA and Lifestyle study were used for the discovery group ( n  = 1615). Genotype data for six SNPs selected to cover most variation in the TACR1 gene were used to test for an association with symptomatic OA. Replication analysis was performed using data from the Chingford 1000 Women Study, Hertfordshire Cohort Study, Tasmanian Older Adult Cohort Study and the Clearwater OA Study. In total, n  = 1715 symptomatic OA and n  = 735 asymptomatic OA individuals were analysed. Results: Out of six SNPs tested in the TACR1 gene, one (rs11688000) showed a nominally significant association with a decreased risk of symptomatic OA in the discovery cohort. This was then replicated in four additional cohorts. After adjusting for age, gender, body mass index and radiographic severity, the G (minor) allele at rs11688000 was associated with a decreased risk of symptomatic OA compared to asymptomatic OA cases ( p  = 9.90 × 10 −4, OR = 0.79 95% 0.68–0.90 after meta‐analysis). Conclusions: This study supports a contribution from the TACR1 gene in human OA pain, supporting further investigation of this gene's function in OA. Significance: This study contributes to the knowledge of the genetics of painful osteoarthritis, a condition which affects millions of individuals worldwide. Specifically, a contribution from the TACR1 gene to modulating pain sensitivity in osteoarthritis is suggested.